Desenvolvimento de um dispositivo inovador de simulação dinâmica do sistema respiratório para avaliação de um TNT revestido com filme de Cu - Dapper, Gabriel Justen (My University, 2022)
Protective face masks act as the first defense line against pathogens that already exist and those that may emerge over the time, their importance has been proven during the recent COVID-19 pandemic. The development and validation of functional materials for application in these equipment is very important, since they contribute directly to the bacterial and viral inoculum reduction, consequently, in the symptoms attenuation of numerous diseases. An innovative test equipment for dynamically evaluating fabrics was developed in this work, which allows breathability analysis, film leaching evaluation, bacteria and viruses inoculation simulation through aerosols and simulation of a user's breathing. It was also possible to evaluate the morphological, physical-chemical and biological performance properties of a polypropylene (C3H6)n nonwoven fabric coated with copper (Cu) film. Different concentrations of Cu were deposited by the magnetron sputtering process. By scanning electron microscopy (SEM/FEG) and energy dispersion spectroscopy (EDS) techniques, it was observed that the Cu film was uniformly deposited, and the concentration is directly proportional to the target exposure time. It was possible to evaluate the cytotoxic activity of the obtained composite by the MTT indirect method using the L929 mouse fibroblasts, which showed no cytotoxic effects at low Cu concentration. Once Cu concentration increased in a fold of four times higher than the lower exposition time, samples maintained cell viability at acceptable levels. The antimicrobial activity of the obtained composite was evaluated by AATCC TM 147 procedure and by the resazurin technique for strains Escherichia coli AATCC 25922 and Staphylococcus aureus AATCC 25923, for which, results of expressive antimicrobial activity were obtained for samples with high Cu concentrations. Through the fabricated test equipment, it was concluded that: the TNT permeability coefficient is equivalent to 71,4 Pa.cm-2 and there is no leaching of the deposited Cu film of the nonwoven. It was possible to evaluate the antimicrobial activity of the nonwoven with the maximum Cu concentration against the E. coli bacteria under dynamic conditions. The dynamic condition adopted for the test consists of: alternating pulses of pressure and relief generated by the test equipment conduct the bacterial aerosol through the nonwoven fabric under test, simulating the inoculation by a user. [resumo fornecido pelo autor]
Máscaras de proteção facial atuam como primeira linha de defesa contra patógenos existentes e que podem surgir com o passar do tempo, sendo sua importância comprovada durante a recente pandemia de COVID-19. É de fundamental importância o desenvolvimento e validação de materiais funcionais para aplicação nestes equipamentos que contribuem diretamente na redução do inóculo de agentes bacterianos e virais e consequentemente, na atenuação dos sintomas de inúmeras doenças. Desenvolveu-se neste trabalho um dispositivo de teste inovador para avaliação de tecidos de forma dinâmica, que permite análise de respirabilidade, avaliação de lixiviação de filmes, simulação de inoculação de bactérias e vírus através de aerossóis e simulação de respiração de um usuário. Também foi possível avaliar as propriedades morfológicas, físico-químicas e de desempenho biológico de um tecido não tecido (TNT) de polipropileno (C3H6)n revestido com filme de cobre (Cu). Foram depositadas diferentes concentrações de Cu pelo processo de magnetron sputtering. Pelas técnicas de microscopia eletrônica de varredura (MEV/FEG) e de espectroscopia de dispersão em energia (EDS) observou-se que o filme de Cu foi depositado de forma uniforme e, que a concentração é proporcional ao tempo de exposição ao alvo de deposição. Avaliou-se a atividade citotóxica do compósito obtido pelo método indireto de MTT frente aos fibroblastos de camundongo L929, para os quais, as amostras com baixa concentração de Cu não apresentaram efeito citotóxico. Uma vez que a concentração de Cu aumentou quatro vezes mais do que o menor tempo de exposição, as amostras mantiveram a viabilidade celular em níveis aceitáveis. Avaliou-se a atividade antimicrobiana do compósito obtido pelo procedimento AATCC TM 147 e pela técnica de resazurina para as cepas Escherichia coli AATCC 25922 e Staphylococcus aureus AATCC 25923, para as quais, observou-se atividade antimicrobiana significativa para as espécies com concentrações elevadas de Cu. Por meio do dispositivo de teste construído, concluiu-se que: o coeficiente de permeabilidade do TNT equivale a 71,4 Pa.cm-2 e não há lixiviação do Cu depositado do TNT. Também foi analisada a atividade antibacteriana do tecido com a concentração máxima de Cu frente a cepa E. coli em condições dinâmicas. A condição dinâmica adotada para o teste consiste em: pulsos alternados de pressão e alívio gerados pelo equipamento conduzem o aerossol bacteriano através do tecido em teste, simulando a inoculação por um usuário. [resumo fornecido pelo autor]
Keywords: Aparelho respiratório - Proteção; Máscara; Agentes anti-infecciosos; Tecidos; Cobre; Respiratory organs - Protection; Gas masks; Anti-inflammatory agents; Textile fabrics; Copper